Precipitating factors, clinical features and outcome of diabetic ketoacidosis in children and adolescents admitted in a tertiary care hospital in Dhaka (Bangladesh Journal of Medical Science, 2013)
Background Information: Diabetic ketoacidosis (DKA) is the leading cause of morbidity and mortality in children with type 1 diabetes mellitus (DM). It is an acute complication of type 1 DM. Objective: This study was designed to identify the precipitating factors, clinical features and immediate outcomes of DKA in children and adolescents. Method: This was a retrospective study which was done in the department of Pediatrics, BIRDEM, from January 2002 to April 2007. Data were collected from the hospital record for all diabetic children below 18 years admitted with DKA. Result: Fourty nine children and adolescents were admitted with DKA. Sixty one percent were known cases and the remaining (39%) were new DM. Majority were female (63%). Most (49%) of the children were between 11- 15 years. Infection was the commonest (49%) precipitating factor followed by insulin omission (24%). Major clinical features were kussmaul breathing (94%) and dehydration (94%).Eighty eight percent patients improved after treatment and mortality was 12%. Conclusion: Infection was the commonest precipitating factor of DKA. Kussmaul breathing and dehydration were the commonest clinical features. Most of the patients improved after treatment.DOI: http://dx.doi.org/10.3329/bjms.v13i1.17429 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 53-57